Assessment of Dual Rinse Combined with Sodium Hypochlorite Irrigating Solution on Post-Instrumentation Pain and Bacterial Load Reduction: A Randomized Clinical Trial - Abdel-Hamid, Laila Zakaria Ismail; El Boghdadi, Randa Mohamed; Gawdat, Shaimaa Ismail; Salem, Sherifa Tarek; Soliman, Noha Salah (Brazilian Dental Science, 2024)
Objective: The study compared the efficacy of Dual Rinse combined with sodium hypochlorite in comparison to sodium hypochlorite irrigating solution on post instrumentation pain incidence, reduction of the load of intracanal bacteria and periapical MMP-9 expression in patients with pulp necrosis. Material and Methods: Thirty-four patients diagnosed with a necrotic mandibular premolar having a single root canal were included. Following confirmation of the diagnosis, patients were randomly allocated into one of two groups of 17 patients each (intervention group; Dual Rinse + 2.5% NaOCl, control group; 2.5% NaOCl irrigation). Standard endodontic treatment was done in two visits. Post-instrumentation pain was assessed at 6, 12, 24 hours and 48 hours using Heft-parker visual analogue scale (Heft parker VAS). The intracanal bacterial levels assessed pre- and postinstrumentation through counting of CFU/mL. Periapical MMP-9 levels were assessed post-instrumentation and pre-obturation by ELISA. All data collected from patients was statistically analyzed. Results: Regarding postinstrumentation pain incidence, there was no statistically significant difference detected among tested irrigants at all time intervals (p>0.05). There was a significant reduction in the count of intracanal bacterial in both groups after instrumentation, but without any significant difference between tested irrigants (p>0.05). Within a week, there was a considerable drop in the periapical MMP-9 levels without any discernible differences between the two irriagnts (p>0.05). Conclusion: The addition of Dual Rinse to 2.5% NaOCl solution did not result in any apparent increase in the incidence of post-instrumentation pain or in periapical MMP-9 levels. Both irrigating solutions were almost equally successful in lowering the amount of bacteria in primary infected root canals while maintaining the antibacterial activity of the NaOCl. KEYWORDS Bacterial load reduction; Dual rinse in sodium hypochlorite; Irrigation; Matrix metalloproteinase (MMP-9); Post-instrumentation pain.